Enhancing the efficiency of mortar mixes by rice husk hydrochar using response surface methodology: An experimental study for property improvement and sustainable construction applications - Lafiya Shanavas Laila; Kavitha M․Sambasivam (Results in Engineering, 2025)
This article explores the influence of hydrochar, prepared from rice husk, its optimization, characterization and its cementitious applications. Response Surface Methodology (RSM) was used to optimize the hydrochar production at 200 °C, 3 h, and a W/B ratio of 1:0.31 were the best conditions for maximizing yield. Rice husk was selected owing to its high pozzolanic reactivity, low lignin content, and abundant availability. The optimized hydrochar was characterized using field emission scanning electron microscopy (FESEM), Powder X-ray diffraction (PXRD), Fourier-transform infrared spectroscopy (FTIR), Thermogravimetric analysis (TGA), and Brunauer–Emmett–Teller (BET) surface area analysis. Ultrasonic Pulse Velocity (UPV) analysis showed a strong correlation with mechanical properties, supporting its use as a reliable non-destructive testing method. Microstructural and PXRD analyses showed that low hydrochar dosages (≤1.5 %) had minimal impact on hydration phases. In contrast, higher dosages (>3 %) led to a reduction in portlandite and promoted the formation of C–S–H(calcium silicate hydrates). After 28 days, blended mortars exhibited compressive strengths of 27–41 MPa and flexural strengths of 3.31–4.92 MPa, indicating their potential for applications such as plastering, rendering, masonry, partition blocks, pedestrian paths, and other low-traffic infrastructure.